2010
DOI: 10.1590/s0100-879x2010005000004
|View full text |Cite
|
Sign up to set email alerts
|

IgE cross-reactivity between Lolium multiflorum and commercial grass pollen allergen extracts in Brazilian patients with pollinosis

Abstract: 90% recognition. Lm, Lp and GII extracts significantly inhibited IgE binding to the most immunodominant Lm components, particularly the 55 kDa band. The 26 kDa and 90-114 kDa bands presented the lowest amount of heterologous inhibition. We demonstrated that Lm extract contains both Lm-specific and cross-reactive IgE-binding components and therefore it is suitable for measuring quantitative IgE levels for diagnostic and therapeutic purposes in patients with pollinosis sensitized to Lm grass pollen rather than o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 33 publications
(57 reference statements)
1
5
0
5
Order By: Relevance
“…Several studies have documented the allergens/sensitizing agents and risk factors associated with the increased prevalence of AR and AR/C in the regions of interest .…”
Section: Pattern Of Allergens and Risks Associated With Allergic Diseasementioning
confidence: 99%
“…Several studies have documented the allergens/sensitizing agents and risk factors associated with the increased prevalence of AR and AR/C in the regions of interest .…”
Section: Pattern Of Allergens and Risks Associated With Allergic Diseasementioning
confidence: 99%
“…[5, 6] In the subtropical high altitude zones of Brazil, Lolium multiflorum (Italian or annual ryegrass; subfamily: Pooideae) has been shown to be a major sensitizing pollen source in patients with grass pollen allergy. [7–9] However, also other grass species, such as Anthoxanthum odoratum (sweet vernal grass; subfamily: Pooideae), Cynodon dactylon (Bermuda grass; subfamily: Chloridoideae), Holcus lanatus (common velvet grass; subfamily: Pooideae), Paspalum notatum (bahia grass; subfamily: Panicoideae) and Bromus sp (subfamily: Pooideae) occur there. Cross-reactivity studies with single and mixed natural grass pollen extracts have demonstrated a certain level of cross-reactivity between Lolium multiflorum and other grasses in this region, but the clinical relevance of this finding has not yet been investigated using recombinant allergens.…”
Section: Introductionmentioning
confidence: 99%
“…Os estudos com alergia a Lolium multiflorum ainda são raros, ao se considerar que esta planta é uma das mais importantes fontes de alérgenos como causadora de rinite alérgica sazonal no sul do Brasil (BERNARDES et al, 2010 nasal, espirros, rinorréia, prurido nasal e/ou ocular, dentre outros (MELTZER, 2016;MELTZER et al, 2009). Além disso, a qualidade de sono dos indivíduos adultos alérgicos é majoritariamente afetada pela doença, sendo que um estudo demonstrou haver um excesso de micro despertares durante o sono, afetando sua qualidade e produtividade durante o dia (LAVIE et al, 1981).…”
Section: Discussionunclassified
“…Dentre essas proteínas, os alérgenos do grupo 1, que estão presentes em todas as subfamílias de Poaceae, e são denominados -expansinas podem constituir até 10% de todo grão de pólen. Como representantes dessas proteínas se destacam, (BERNARDES et al, 2010;MOREIRA et al, 2015;SOPELETE et al, 2006). Um recente estudo, mostrou que L.…”
Section: Polensunclassified
See 1 more Smart Citation